Psychological Impact Of Covid-19 Among The Old Aged People (International Journal of Food and Nutritional Sciences, 2022)
The current Coronavirus disease (COVID-19) pandemic is a particular and rare situation and has raised international concern and this pandemic has caused ruin far and wide. India is also facing a difficult circumstance as the quantity of infected /positive cases is expanding step by step. With exacting preventive measures and limitations by the Indian Government as across the nation lockdown, the peoples are going through a range of psychological and emotional problems, fear and havoc being one of them. But COVID-19 is changing older people‟s daily schedules, the consideration and bolster they get, their capacity to remain socially connected, and how they are seen. Older adults are consistently reported to be more vulnerable to COVID-19.This study was conducted to explore the “Psychological impact of covid-19 among the old aged people”. The Geriatric Depression Scale (GDS) is a 30-item selfreport assessment used to identify depression in the elderly. The scale was first developed in 1982 by J.A. Yesavage and others, to assess depression, and Mental Health Checklist developed by P Kumar to assess the mental health of elder people. The sample size was 60 respondents (30 male and 30 female). Finding of Mean, SD, t-test and the Pearson Product moment Coefficientof correlation(r test) revealed that depression and mental health are correlated significantly. Also, Poor mental health status, depression was found to be high in elderly female groups of age range 55 -60 above.